Silver nanoparticles on dragon fruit in vitro germination and growth - de Oliveira Timoteo, Caroline; Paiva, Renato; Valquíria dos Reis, Michele; Pedrosa Corrêa da Silva, Diogo; Raphaella da Silva, Bruna; Elvis de Oliveira, Juliano (Plant Cell Culture & Micropropagation - ISSN 1808-9909, 2023)
Silver nanoparticles (AgNPs) have different physicochemical properties compared to their counterparts that occur on the macro scale. Due to these properties, it has been used in a variety of medicinal products, pharmaceuticals, food packaging, dyes, cosmetics, biosensors, electronics and agriculture. However, although there are attempts to determine possible toxic effects of AgNPs, the results are still inconclusive, since the phytotoxicity of the nanoparticles in plant species is dependent on the species and the concentration of AgNPs to which they are exposed. Thus, the objective of this study was to evaluate the phytotoxicity of AgNPs on the in vitro cultivation of the cactus Hylocereus undatus (dragon fruit). For this purpose, dragon fruit seeds were inoculated in 1/4 MS culture medium supplemented by different concentrations of AgNPs. Subsequently, the seedlings were acclimatized. After 90 days of in vitro cultivation, it was observed that the presence of AgNPs did not affect dragon fruit germination, as well as the length of the cladodium. However, longer roots were observed in the presence of 8 mg L-1 of AgNPs. In acclimatization, the plants from in vitro cultivation with AgNPs showed a higher number of shoots. These results indicate that the tested concentrations of AgNPs showed no in vitro cultured dragon fruit toxicity.